Review of Remediation Goals at Contaminated Sediment Sites in the United States. (7th August 2019) - Pelletier, Derek; Sacks, Victoria Paris; Sorensen, Mary; Magar, Victor
ABSTRACT: Remediation decisions for contaminated sediment sites are typically based on comparisons of in situ sediment concentrations to preliminary remediation goals (PRGs). Preliminary remediation goals are typically developed for protection of human health and the environment, with consideration of site‐specific factors that play an important role in determining the sediment concentrations that are consistent with the human health and environmental protection objectives. Remediation goals are selected from among the PRGs. Sediment remediation goals for 4 common contaminants (PCBs, PAHs, Pb, and Hg) at contaminated sediment sites throughout the United States were compiled to determine significant trends and evaluate causes of those trends. Remediation goals were compiled from Records of Decision (RODs) and 5‐year review reports for 77 contaminated sediment sites throughout the continental United States. Remediation goals were developed both as surface‐weighted average concentrations (SWACs) and action levels (i.e., not‐to‐exceed values). One or both may be used to define areas requiring remediation. Remediation goals based on SWACs are typically applied to bioaccumulative chemicals for human health and wildlife receptors, whereas action levels are typically used for chemicals that result in an acute toxicity to small home range, sediment‐dwelling biota. The findings from this review of remediation goals indicate that SWACs are an increasingly common approach for developing remediation goals. In addition, the findings from this review indicate that although remediation goals adopted for Pb have become more stringent over time, no trend is evident for PCBs, PAHs, and Hg. Remediation goals for PCBs, PAHs, and Hg vary among a number of factors, such as geography, habitat, human or ecological risks, and other local factors. Integr Environ Assess Manag 2019;15:772–782. © 2019 SETAC. Key Points: This compilation presents an unbiased evaluation of sediment remediation goals from sites throughout the United States based on a review of 30+ years of decision documents on the US Environmental Protection Agency's website. Sediment remediation goals at contaminated sites are highly variable and driven by site‐specific considerations related to factors such as environmental setting and relevant receptors and exposure pathways. Surface‐weighted average concentration (SWAC)–based remediation goals for bioaccumulative chemicals (e.g., PCBs and Hg) have increasingly been adopted at contaminated sediment sites throughout the United States.